Incidence and Sonographic Detection of Fetal Anomalies in Pregnancies Complicated by Polyhydramnios - Tosun, Miğraci; Çelik, Handan; Erdoğan, Özgür; Malatyalıoğlu, Erdal; Çetinkaya, Mehmet; Altunsoy, Süleyman (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: The purpose of this study was to evaluate the incidence and sonographic detection of fetal anomaly related with polyhydramnios and to estimate the relationship between fetal anomaly and the severity of polyhydramnios and to compare the idiopathic polyhydramnios with polyhydramnios associated with fetal anomaly. STUDY DESIGN: This was a prospective study of 60 singleton pregnancies with polyhydramnios. Though all singleton pregnancies with polyhydramnios were included, only the patients with idiopathic polyhydramnios or with fetal anomalies were the object of this study. Idiopathic polyhydramnios was defined as polyhydramnios that is not associated with congenital anomalies, fetal chromosomal abnormalities, fetal infections, maternal diabetes, placental tumors or isoimmünization. Polyhydramnios was defined as 25 cm or greater amniotic fluid index. Polyhydramnios was categorized as mild (amniotic fluid index of 25-29,9 cm) and severe (amniotic fluid index of 30 cm or more). The prevalence of fetal anomalies was analyzed according to the severity of polyhydramnios. RESULTS: Polyhydramnios was diagnosed in 60 patients. Of the 60 patients, 33 were considered to have idiopathic polyhydramnios (55 %), and of the remaining, 22 patients (37%) were associated with fetal anomalies. There was statically significant difference between these two groups in respect to amniotic fluid index. In patients with fetal anomaly, amniotic fluid index was significantly higher than in patient with idiopathic polyhydramnios (p=0.001). In 55 patients, mild polyhydramnios was observed in 43 pregnancies (78%) and severe polyhydramnios was noted in 12 pregnancies (22%). The prevalence of congenital anomaly was increased significantly with the severity of polyhydramnios (p=0,001). The number of fetal anomaly was 11 (25%) in mild polyhydramnios group, 11 (91%) in severe polyhydramnios group. CONCLUSION: It is reasonable to distinguish between mild and severe polyhydramnios regarding special attention and antenatal follow-up as fetal anomaly is related to the degree of polyhydramnios. Significant risk of fetal anomalies should be considered in patients with severe polyhydramnios (AFI≥ 30 cm).